Rethinking the University: A Pedagogy for the Present from Paulo Freire - Bolo Romero, Karla Mabel (2021)
This research considers if Paulo Freire’s thought has validity to address contemporary problems of education and its social and cultural implications within the University. It focuses on the aspects that have influenced on the way in which education is conducted and its link with social facets. To this end, the main pedagogical categories Freire presents in his “Pedagogy of the oppressed” are analyzed, such as awareness, banking education and freedom, as well as the social character of his “Pedagogy”, his openness to racial and gender problems, and its connection within the University.